การศึกษาฤทธิ์ลดน้ำตาลในเลือดและความเป็นพิษเรื้อรังของไมยราบ - เดชาติวงศ์ ณ อยุธยา, ขวัญฤดี; ทัพยุทธพิจารณ์, พิมลวรรณ; หิญชีระนันทน์, ธริส; รัตนระพี, สำเริง; พิเดช, พรรณี (Journal of Basic and Applied Pharmacology, 2015)
Extraction and fractionation of whole dried plants of Minosa pudica Linn were performed. The yields obtained were alcoholic extract, petroleum ether extract, flavonoids, tertiary and quaternary alkaloids respectively. The hypoglycemic effects of these extracts were studied in normal and streptozotocin induced diabetic rats. The blood sugar lowering activities of all those fractions, except the flavonoids and tertiary alkaloids could be demonstrated in diabetic rats in the second hour after single oral dose and reached to the maximum in six hours. By thin layer chromatography with various solvent systems, the constituents in the plant could be detected. They were phenols, terpenes, sugars and steroids. The active principle in those three active fractions seem to be different. According to some toxicity reports of the extract, three concentrations of the decoction were given orally once daily to for a period of 6 months. No abnormal symptoms were observed. The peripheral blood picture, liver function and histological findings of the lung, kidney and liver were also within normal limits. However, further studies should be made to clarify the therapeutic value of this plant.